1997
DOI: 10.1128/mcb.17.2.1027
|View full text |Cite
|
Sign up to set email alerts
|

Altered Replication and Inverted Repeats Induce Mismatch Repair-Independent Recombination between Highly Diverged DNAs in Yeast

Abstract: Replication, DNA organization, and mismatch repair (MMR) can influence recombination. We examined the effects of altered replication due to a mutation in the polymerase ␦ gene, long inverted repeats (LIRs) in motifs similar to those in higher eukaryotes, and MMR on intrachromosomal recombination between highly diverged (28%) truncated genes in Saccharomyces cerevisiae. A combination of altered replication and an LIR increased recombination up to 700-fold, while each alone led to a 3-to 20-fold increase. Homeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 59 publications
(107 reference statements)
3
22
0
Order By: Relevance
“…Unlike USCR, the other mechanisms do not require that DNA replication has proceeded through the recombination substrate, suggesting that direct repeat recombination (DRR) may not be restricted to S and G 2 phases. The results of our experiments were similar to those from a number of studies that have demonstrated that the pol3-t mutation can increase the rate of DRR (Tran et al 1997;Lobachev et al 1998, 13 (27) 2 (4) 0 (0) 8 (17) 0 (0) 0 (0) 19 (40) 1 (2) 3 (6) pol3-t rev1D…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Unlike USCR, the other mechanisms do not require that DNA replication has proceeded through the recombination substrate, suggesting that direct repeat recombination (DRR) may not be restricted to S and G 2 phases. The results of our experiments were similar to those from a number of studies that have demonstrated that the pol3-t mutation can increase the rate of DRR (Tran et al 1997;Lobachev et al 1998, 13 (27) 2 (4) 0 (0) 8 (17) 0 (0) 0 (0) 19 (40) 1 (2) 3 (6) pol3-t rev1D…”
Section: Resultssupporting
confidence: 79%
“…In particular, mutations that disrupt the polymerase function of Pol d confer increased rates of mutation and recombination (Gordenin et al 1992;Tran et al 1995Tran et al , 1996Tran et al , 1997Kokoska et al 1998Kokoska et al , 2000Lobachev et al 1998Lobachev et al , 2000Galli et al 2003), consistent with incom- 18.8 (9.3-24.1) 4.2 9.6 (6.7-11.4) 5.7 pol3-t rev7D…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The present study considerably extends our recent report demonstrating a reduction in closely spaced inverted Alus as compared to direct Alu repeats (Lobachev et al 2000). Based on results from model systems, other factors also are likely to be important in the stability of Alu sites including genetic background (Gordenin et al 1993;Ruskin and Fink 1993;Tran et al 1997;Lobachev et al 1998Lobachev et al , 2000). For example, recombination in mammalian cell constructs containing direct identical Alu repeats is high in p53 defective as compared to p53 wildtype cells (Gebow et al 2000).…”
Section: Discussion General Approach To Investigating Alu Distributionsupporting
confidence: 66%
“…Pairs of large inverted DNA repeats can be unstable, lead to deletions, and stimulate recombination between DNAs surrounding the inverted repeats in yeast (Gordenin et al 1993;Ruskin and Fink 1993;Nag and Kurst 1997;Tran et al 1997;Lobachev et al 1998Lobachev et al , 2000 ) and mammalian cells (Akgun et al 1997;Lewis 1999;Lewis et al 1999). Sequence identity was suggested as a likely factor in the stability of Alu repeats based on results in yeast.…”
Section: Discussion General Approach To Investigating Alu Distributionmentioning
confidence: 99%